1997
DOI: 10.1007/s002560050242
|View full text |Cite
|
Sign up to set email alerts
|

MR diagnosis of traumatic tear of the spring ligament in a pole vaulter

Abstract: The spring ligament is a significant contributor to the stability of the talar head and longitudinal arch of the foot, lending importance to accurate radiologic diagnosis of injury. Using MR, we diagnosed a spring ligament tear with associated navicular dorsal subluxation, confirmed intraoperatively. To our knowledge, there are no previous reports of MR diagnosis of tear of the spring ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The imaging literature on the spring ligament complex is sparse (14,15,23,24). Yao et al reported MR imaging findings in 13 cases of surgically proved spring ligament insufficiency (14).…”
Section: Discussionmentioning
confidence: 98%
“…The imaging literature on the spring ligament complex is sparse (14,15,23,24). Yao et al reported MR imaging findings in 13 cases of surgically proved spring ligament insufficiency (14).…”
Section: Discussionmentioning
confidence: 98%
“…The imaging features of spring ligament tears and insufficiency have been well described [3,4]. While tears are best diagnosed by frank discontinuity of the ligament fibers [5,10], the diagnosis of insufficiency is made by signal heterogeneity, attenuation, or thickening of the liga-ment. Acute spring ligament tears are related to trauma as opposed to spring ligament insufficiency, which is the result of gradual ligament attrition and stretching.…”
Section: Discussionmentioning
confidence: 99%
“…
Much has been written describing the normal and pathologic MR features of the spring ligament [2][3][4][5][6]. To our knowledge, however, there has not yet been a study reporting the presence and the imaging features of the spring ligament recess, a fluid collection extending from the talocalcaneonavicular joint, interposed between the medioplantar oblique and inferoplantar longitudinal components of the spring ligament.
…”
mentioning
confidence: 99%
“…The condition is typically seen in middle-aged women and may result in an acquired flatfoot [5]. There is usually no history of trauma, although acute injury of the spring ligament has been reported [19,20]. The pathology is usually confined to the superomedial CNL.…”
Section: Discussionmentioning
confidence: 95%
“…In one case, the PTT was considered normal. Although spring-ligament dysfunction is classically associated with posterior tibial tendinosis, it is recognised that the spring ligament may be torn in isolation [19,20].…”
Section: Discussionmentioning
confidence: 99%